Information about CIB W-51 Acoustics Meeting in Warsaw - 25-27 May 1994 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1995)
The Information Council for Building Research Studies and Documentation is an international organization concerned with studies, research and documentation in the building industry. It unites 70 countries. It has over 500 collective and individual members.